An empirical analysis of sustainability of trade deficit: Evidence from Sri Lanka - Perera, Nelson; Verma, Reetu (2007)
In this paper, the long-run relationship between Sri Lanka exports and imports during the period 1950 to 2006 is examined using unit root tests and co-integration techniques that allow for an endogenously determined structural break. The results failed to support the existence of a long-run equilibrium between exports and imports in Sri Lanka. This finding questions the effectiveness of Sri Lanka’s current long-term macroeconomic policies and suggests that Sri Lanka is in violation of its international budget constraint.